2018
DOI: 10.1177/0044118x18760647
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Romantic Relationship–Oriented Facebook Behaviors: Implications for Self-Esteem

Abstract: Despite the consistent, high use of Facebook among adolescents, few studies have examined how adolescents use Facebook when forming and maintaining romantic relationships. Based on the Internet-enhanced self-disclosure hypothesis, romantic relationship–oriented Facebook behaviors are likely to relate to adolescent self-esteem. The goal of this study is to examine romantic relationship–oriented Facebook behaviors (private exchanges, monitoring, public displays, and oversharing information) between adolescents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although Facebook is used less often than other social media sites (Anderson & Jiang, ), some adolescents report using this popular site as a means of monitoring others in which they are romantically attracted (i.e., a crush), but such monitoring was associated with reduced feelings of self‐esteem. For those in romantic relationships, Facebook served as a means to publicly share that they were in a relationship (i.e., being Facebook official; Langlais, Gwendolyn, & Bruxvoort, ).…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…Although Facebook is used less often than other social media sites (Anderson & Jiang, ), some adolescents report using this popular site as a means of monitoring others in which they are romantically attracted (i.e., a crush), but such monitoring was associated with reduced feelings of self‐esteem. For those in romantic relationships, Facebook served as a means to publicly share that they were in a relationship (i.e., being Facebook official; Langlais, Gwendolyn, & Bruxvoort, ).…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…For example, some studies show that students used Facebook to a low extent (Gordon et al, 2023;Palazon et al, 2015;Taipe et al, 2023). In contrast, others have shown that students' use of Facebook was high (Ilakkuvan et al, 2019), especially for viewing sexual content (Langlais et al, 2020;Stănculescu & Griffiths, 2021;Owan et al, 2020), narcissism, self-identity and empowerment (Gulatee et al, 2021), and other non-educational purposes (Zagidullin et al, 2021). Since the results of previous studies tend to show high use of Facebook for noneducational purposes, the first hypothesis of this study was developed.…”
Section: Facebook Use Among Higher Education Studentsmentioning
confidence: 96%
“…Among adolescents, it has been found that romantic-partner monitoring on Facebook is significantly related to lower self-esteem of the perpetrator (Langlais, Seidman, & Bruxvoort, 2018). Moreover, it has been found that attachment anxiety is significantly related to engagement in monitoring behaviors among high school youth (Reed et al, 2016).…”
Section: Online Monitoring and Social Media Usementioning
confidence: 99%